2011
DOI: 10.1007/s00253-010-3072-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-mediated PAH degradation in soil and sediment

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the natural environment and easily accumulate in soil and sediment due to their low solubility and high hydrophobicity, rendering them less available for biological degradation. However, microbial degradation is a promising mechanism which is responsible for the ecological recovery of PAH-contaminated soil and sediment for removing these recalcitrant compounds compared with chemical degradation of PAHs. The goal of this review is to provide an outline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(76 citation statements)
references
References 102 publications
1
73
0
2
Order By: Relevance
“…Additionally, the authors found a significant fall in phenanthrene concentration in the spiked sediments which was linked to bacterial metabolism based on quantification of activity of genes (xylE and phnAc dioxygenase genes) involved in PAH degradation. A significant number of papers have been published in the last 10 years which have looked into aspects of isolation of novel bacterial strains from diverse environments including sediments contaminated with PAH compounds (e.g., review by Lu et al 2011).…”
Section: Biodegradation Of Oil Pollutants In Marine Environmentmentioning
confidence: 99%
“…Additionally, the authors found a significant fall in phenanthrene concentration in the spiked sediments which was linked to bacterial metabolism based on quantification of activity of genes (xylE and phnAc dioxygenase genes) involved in PAH degradation. A significant number of papers have been published in the last 10 years which have looked into aspects of isolation of novel bacterial strains from diverse environments including sediments contaminated with PAH compounds (e.g., review by Lu et al 2011).…”
Section: Biodegradation Of Oil Pollutants In Marine Environmentmentioning
confidence: 99%
“…With changes in salinity, the microbial population can sometimes change resulting in less diversity. It has been demonstrated that as salinity increases the degradation rates of hydrocarbons decrease (Atlas 1981) as was the inhibition of degradation of PAHs (polycyclic aromatic hydrocarbons) (Lu et al 2011). The pH in environments is variable depending on the type, in which wetlands tend to have a lower pH, whereas mineral soils have a more neutral or slightly higher pH (Venosa and Zhu 2003).…”
Section: Salinity and Phmentioning
confidence: 98%
“…Nitrate-induced bioremediation has been shown to be an attractive option for remediating the contaminated marine sediment (Hutchins 1991;Wilson et al 1997;Hutchins et al 1998;Shao et al 2010). Nitrate, as an electron acceptor in nitrateinduced bioremediation, is more than ten thousand times more soluble than oxygen in terms of electron-accepting capacity, and it can yield free energy almost as much as that under aerobic conditions (Lu et al 2011). Previous studies have revealed that NO 3 − stimulated the growth of both heterotrophic and autotrophic denitrifiers, and the former can out-compete sulfate-reducing bacteria for organics degradation (Eq.…”
Section: Introductionmentioning
confidence: 98%
“…One of the possible reasons that lead to the low biodegradation efficiency of petroleum hydrocarbons especially the high molecular weight fractions is their low solubility (Villemur et al 2000;Lu et al 2011), which makes them present as non-aqueous pollutant liquids (NAPL) (Martienssen and Schirmer 2007). The organic pollutants can be mainly degraded by microorganisms or some specific enzymes present in solutions, where they are available for microbial action.…”
Section: Introductionmentioning
confidence: 99%